Potential geoheritages in Lao Cai - Suggestions preservation and development - Phuc, La The; Tuyen, Pham Thi Kim; Nga, Kieu Thanh; Nga, Nguyen Thi (Vietnam Journal of Earth Sciences, 2014)
Lao Cai is one of the richest provinces in Viet Nam in terms of geological resources and minerals. Mineral resourceshave been exploited for a long time. They brought numerous economic benefits for the owner. Although geoheritageshave identified in preliminary investigation but they proved to be diverse and of great potential. According to preliminaryresearch, Lao Cai province has 6 types of 10 types of geoheritages in the UNESCO classification, including: type B -Geomorphology; type D - Stone; type E -Stratigraphy; type F - Mineral resources; type H - Geological economy; type I -Tectonic; type L - Geological characteristics continent/ocean. In this, the geoheritage type B (landscape, waterfall, cave),which has been exploited since the middle of last century to present, brought real economic effects. However, theexploitation of geoheritages is still in low level. The definition of geoheritage has not been clarified yet, and the issues ofconservation and promotion of geoheritages are insufficient. The paper introduces briefly the potential of geoheritagesaccording to the preliminary research and proposes possible measures of conservation and development ofgeoheritages in Lao Cai.ReferencesBùi Phú Mỹ (chủ biên), 2004. Bản đồ địa chất và khoáng sản tờ Kim Bình - Lào Cai, tỷ lệ 1:200.000. Cục Địa chất và Khoáng sản Việt Nam, Hà Nội.La Thế Phúc, Trần Tân Văn, 2009. Nghiên cứu di sản địa chất và xây dựng công viên Địa chất ở Việt Nam. TC. Địa chất; loạt A310, tr10-19.La Thế Phúc, Võ Tiến Dũng, Nguyễn Tuấn Anh, 2012. Ứng dụng nghiên cứu di sản địa chất trong quy hoạch khai thác mỏ ở Việt Nam. Tuyển tập báo cáo “Chiến lược phát triển khoáng sản VN từ tầm nhìn đến hành động” - Hội nghị KHKT Mỏ toàn quốc lần thứ 23, tr.30-35.Trần Văn Trị, Vũ Khúc (đồng chủ biên), 2009. Địa chất và Tài nguyên Việt Nam. Nhà xuất bản Khoa học Tự nhiên và Công nghệ, Hà Nội. 589tr.www.laocai.gov.vn